Evaluation of primary health care professional to the video clip of lactation physiology (Revista Contexto & Saúde, 2023)
Introduction: Professionals in Primary Health Care services need to provide guidance based on scientific evidence to nursing mothers and their families to promote learning and enable decision-making and safe practices for establishing and maintaining breastfeeding. These guidelines contemplate the physiology of lactation, which is a complex and abstract content for which the use of Educational Technologies is one of the viable options to promote learning through health education with users. Objective: To evaluate the usability of a video clip for learning of lactation physiology by health professionals from primary care services and identify barriers and facilitators for its use. Methodology: Transverse research applied to the knowledge translation model, with 71 participants who responded to System Usability Scale. Spearman correlation test was used. Results: Usability was excellent with the positive association of the professional to have a child health update (p = 0.023). The barriers were: restricted service time, unavailability of resources to present the music video and resistance of professionals to the use of technologies. The facilitators were: waiting room, prenatal care and childcare. Conclusion: Excellence in evaluation points to the useability potential of the music video in the permanent education of professionals and in health education with users. There is a need to minimize infrastructure and human resources barriers for use in primary care services.